Inquiry Learning and Lesson Study Activities on Improving Mathematical Critical Thinking Ability of Madrasa Students - Zainul Mujtahid; Rohmatul Amna; Amam Taufiq Hidayat; Ucia Mahya Dewi; Widya , (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
Today's mathematics learning requires students to always be active in the learning process because mathematics is a field of science that prioritizes high intellectual quality and not just an informative and theoretical field of knowledge. Critical thinking ability is one of the mathematics students need. Appropriate strategies, approaches, and teaching and learning models are needed to train mathematical abilities. Therefore, teachers are expected to determine the right strategy so that the learning objectives of learning are more optimal. In this study, researchers analyze how the result after implementing inquiry learning strategies and lesson study activities affects students' critical thinking skills. The research population was class XI students of Madrasah Aliyah Mu'allimat NW Pancor, and the sample was determined by a purposive sampling technique of 38 students. The research data was carried out using documentation, questionnaires, observation sheets, and math substance tests. The research was conducted through four cycles of lesson study. After implementing these learning processes, there was found that there was an improvement after implementing inquiry learning model and lesson study activities on improving students' critical thinking skills in mathematics.